The Gene Toolkit Implicated in Functional Sex in Sparidae Hermaphrodites: Inferences From Comparative Transcriptomics - Tsakogiannis, Alexandros; Manousaki, Tereza; Lagnel, Jacques; Papanikolaou, Nikolaos; Papandroulakis, Nikos; Mylonas, Constantinos C.; Tsigenopoulos, Costas S. (Frontiers in Genetics, 2019)
Sex-biased gene expression is the mode through which sex dimorphism arises from a nearly identical genome, especially in organisms without genetic sex determination. Teleost fishes show a great variation in the way sex phenotype forms. Among them, Sparidae, that might be considered as a model family displaying a remarkable diversity of reproductive modes. In this study, we sequenced and analyzed the sex-biased transcriptome in gonads and brain, the tissues with the most profound role in sexual development and reproduction, of two sparids with different reproductive mode: the gonochoristic common dentex, Dentex dentex and the protandrous hermaphrodite gilthead seabream, Sparus aurata. Through comparative analysis with other protogynous and rudimentary protandrous sparid transcriptomes already available, we put forward common male and female-specific genes and pathways that are probably implicated in sex differentiation and sex maintenance in this fish family. Our results contribute to the understanding of the complex processes of sex differentiation, especially in hermaphrodite species and set the groundwork for future experiments by providing a gene toolkit that can improve efforts to control phenotypic sex in fin fish in the ever increasing in importance field of aquaculture.